2017
DOI: 10.1101/199372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The circadian hippocampus and its reprogramming in epilepsy: impact for chronotherapeutics

Abstract: Gene and protein expression displays circadian oscillations in numerous body organs. These oscillations can be disrupted in diseases, thus contributing to the disease pathology. Whether the molecular architecture of cortical brain regions oscillates daily and whether these oscillations are modified in brain disorders is less understood. We identified 1200 daily oscillating transcripts in the hippocampus of control mice. More transcripts (1600) were oscillating in experimental epilepsy, with only one fourth osc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…That said, our findings indicate that there are circadian changes in the molecular landscape of the hippocampus that enable this structure of the brain to switch to different functional modes. As a substantial reprogramming of oscillating transcripts occurs in temporal lobe epilepsy (Debski et al, 2017), our findings may have important implications to advance not only our understanding of circadian rhythmicity during physiological conditions but also to understand the pathogenesis and treatment of this and other chronic disease states.…”
Section: Generalizability and Functional Implicationsmentioning
confidence: 86%
See 1 more Smart Citation
“…That said, our findings indicate that there are circadian changes in the molecular landscape of the hippocampus that enable this structure of the brain to switch to different functional modes. As a substantial reprogramming of oscillating transcripts occurs in temporal lobe epilepsy (Debski et al, 2017), our findings may have important implications to advance not only our understanding of circadian rhythmicity during physiological conditions but also to understand the pathogenesis and treatment of this and other chronic disease states.…”
Section: Generalizability and Functional Implicationsmentioning
confidence: 86%
“…The hippocampus is a subordinate circadian oscillator. Here, more than 10% of genes and proteins show circadian fluctuations (Debski et al, 2017) and are associated with changes in synaptic excitability (Barnes et al, 1977). Learning and memory formation, two functions that are conserved across species and that in mammals rely on the activity of the hippocampal formation, are also modulated by circadian rhythms (Gerstner et al, 2009;Rawashdeh et al, 2018;Ruby et al, 2008;Shimizu et al, 2016;Smarr et al, 2014;Snider et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the oscillatory gene can drive a circadian availability of molecular factors that act in the electrical activity of the brain, resulting in rhythmic fluctuation in neuronal excitability ( 23 , 82 ). Accordingly, a recent study using large-scale approach, demonstrated a diurnal remapping of the circadian molecular landscape in the hippocampus of a mouse model of TLE [( 60 ), preprint publication]. Interestingly, mTOR pathway activity which is increased in epileptic animals demonstrates circadian oscillations ( 40 , 83 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…Partly, this is due to a lack of studies on the rhythmic expression of clock genes in epileptic phases. A recent study, using large-scale approaches, demonstrated a diurnal molecular landscape in the hippocampus of epileptic mice [( 60 ), preprint publication]. However, the potential changes in clock genes across different phases of epileptogenesis have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…2). A recent study using large-scale approaches provided an inventory of 1650 transcripts and 237 proteins undergoing diurnal expression in the hippocampus of a mouse model of mTLE (Debski et al, 2017). Notably, the authors observed that ~30% of the transcripts gain circadian fluctuation only when the brain becomes epileptic, which can contribute to de novo features of the limbic seizure rhythmicity.…”
Section: Uncoupled Oscillatorsmentioning
confidence: 99%